William Louis Poteat : A Leader of the Progressive-Era South - Hall, Randal L., 1971- (Book collections on Project MUSE., 2000)
"Poteat also embodied the struggle with the intellectual compromises that tortured contemporary social critics in the South. Though he took a liberal position on numerous issues, he was a staunch advocate for prohibition and became a strong supporter of eugenics, a position he adopted after following his beliefs in a natural hierarchy and absolute moral order to their ultimate conclusion." "Randal Hall's revisionist biography presents a nuanced portrait of Poteat, shedding new light on southern intellectual life, religious development, higher education, and politics in the region during his lifetime."--Jacket.